EKSISTENSI MAKNA TIDUR DALAM AL-QUR’AN: KAJIAN TAFSIR TEMATIK - Rifkal Fadillah, Muh; Nurfadhilah Syam; Mukmin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Sleep is a part of Allah's creation system that has biological, mental, and spiritual dimensions. The purpose of this research is to explain the meaning and wisdom of sleep in the Qur'an through a thematic interpretation approach, exploring its philosophical values and functions as a divine law that maintains the balance of the physical and spiritual aspects, as well as assessing its relevance to modern life. The method used is descriptive-analytical qualitative research based on literature studies. The primary data consists of verses from the Qur'an related to sleep (naum) along with explanations from Tafsir Al-Munīr, Al-Marāghī and Al-Mishbah. The secondary data includes supporting literature and scientific publications (books, journals, theses and dissertations). The analysis is conducted by grouping verses related to sleep, then interpreting their meanings, functions and wisdom from biological, spiritual and theological perspectives. The results of the study show that the Qur'an depicts sleep as a divine mechanism for physical recovery, inner peace and a reminder of human limitations. QS. Al-Baqarah [2]:255 emphasizes the perfection of Allah swt who does not sleep; QS. Al-Furqān [25]:47 explains sleep as a means of recovery and QS. Al-Nabā’ [78]:9 describes it as a time for total rest. Through thematic interpretation, sleep is understood to have multidimensional functions and remains relevant in shaping a healthy, harmonious and balanced lifestyle in the modern era.